Variability in agricultural and biological yields of ten musa genotypes evaluated for two cropping cycles in a subhumid environment of Nigeria - Baiyeri, K.P.; Tenkouano, A. (Informa UK Limited, 2008)
The harvest index (HI), which is the ratio of the economic yield to the aboveground plant biomass, is an important trait to assess progress in improving yield potential. Therefore, a study was carried out to examine the assimilate partitioning of nine Musa hybrids along with a local check for two cropping cycles. Highly significant (P < 0.01) genotype effects were found for all the measured components of yield. Most hybrids displayed HI values that were twice as large as that of the local check, indicating a greater efficiency of hybrids in assimilate partitioning. Genotype-by-cropping cycle interaction for HI was significant, suggesting that resource availability during the two cropping cycles influenced assimilate-partitioning pattern. Correlation coefficients between bunch weight and plant biomass, and between bunch weight and number of fruits per bunch were positive, high and significant. Also, positive and high correlation coefficient was obtained between bunch weight and HI. Furthermore, path coefficient analysis revealed that the direct effects of plant biomass and HI were high; however, the direct effect of number of fruits per bunch was insignificant; rather, its contribution to bunch weight was through an indirect effect via plant biomass. The high direct effect of HI on bunch weight suggested that further yield increase in Musa germplasm is possible by selecting for high HI. But a low and non-significant relationship between plant biomass and HI suggested that increase in yield could be achieved without a proportional increase in biomass.